Futures Market Efficiency in the Soybean Complex - Rausser, Gordon C.; Carter, Colin (The Review of Economics and Statistics, 1983)
13'1 rev . .:. Division of Agricultural Sciences UNIVERSITY OF IFORNLA Working Paper No. 139 R.I>J: FUTURES MARKET EFFICIENCY IN THE SOYBEAN COMPLEX Gordon C. Rausser and Colin Carter GIANNINI FOUNDATION OF AGRICULTURAL. ECONOMICS L.IBRAIli'V iM· ( California Agric'u l tural ElqIeriment Station Giannini Foundation of Agricultural Economics March 1982